2018
DOI: 10.1253/circj.cj-18-0312
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Cardiovascular Surgery for Patients With Dementia as Evaluated by Mini-Mental State Examination

Abstract: Background: The strategy for cardiovascular surgery in dementia patients is controversial, so we aimed to investigate whether preoperative dementia and its severity might affect the outcomes of cardiovascular surgery by evaluating with the Mini-Mental State Examination (MMSE). Methods and Results: The study group comprised 490 patients undergoing cardiovascular surgery. Their preoperative cognitive status was evaluated using the MMSE, and analysis was performed to compare the patients with MMSE score <24 (deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 26 publications
(15 reference statements)
1
28
1
1
Order By: Relevance
“…In the ROOBY trial, preoperative baseline cognitive analyses were performed, and more than 20% of patients showed MCI. Additionally in this study, less than 10% of patients were diagnosed as dementia at baseline 29) , which was similar to the reported ratio of dementia in the study by Yoshimoto and our own institution 22,28) . Silbert et al reported that some cognitive impairment was presented in ap-…”
Section: Bypass Grafting Patients In Aging Societysupporting
confidence: 91%
See 1 more Smart Citation
“…In the ROOBY trial, preoperative baseline cognitive analyses were performed, and more than 20% of patients showed MCI. Additionally in this study, less than 10% of patients were diagnosed as dementia at baseline 29) , which was similar to the reported ratio of dementia in the study by Yoshimoto and our own institution 22,28) . Silbert et al reported that some cognitive impairment was presented in ap-…”
Section: Bypass Grafting Patients In Aging Societysupporting
confidence: 91%
“…In 2018, we analyzed the outcomes of cardiovascular surgery for patients with preoperative dementia and reported the optimal strategy evaluating by MMSE score 22) . The study group included 490 elderly patients, and the preoperative cognitive status was evaluated using MMSE, which had maximum score of 30 points, assessing cognitive functions in orientation, registration, attention, calculation, recall and language 18) .…”
Section: Bypass Grafting Patients In Aging Societymentioning
confidence: 99%
“…At enrollment, participants completed a comprehensive evaluation including but not limited to a physical examination, frailty assessment, medical record and medication review, clinical interview with questionnaires, emotional assessment and a neuropsychological assessment. Participants were excluded if they had a cognitive score consistent with dementia, de ned as a Mini Mental State Examination (MMSE) cut-off score ≥24 (49,50). Participants were also excluded if they were missing covariate data ( Figure 1 lists exclusion details).…”
Section: Participants and Settingmentioning
confidence: 99%
“…At enrollment, participants completed a comprehensive evaluation including but not limited to a physical examination, frailty assessment, medical record and medication review, clinical interview with questionnaires, emotional assessment and a neuropsychological assessment. Participants were excluded here for a cognitive diagnosis other than non-dementia, which were de ned in accordance with the MiniMental State Examination (MMSE) cut-off score ≥ 24 (34,35) (Figure 1 lists exclusion details).…”
Section: Participants and Settingmentioning
confidence: 99%